Diatom-based summer sea surface temperatures (SSST) and winter sea ice cover (WSI) reconstructions for sediment core PS58/270-5 - Struve, Torben; Lamy, Frank; Gäng, Frederik; Klages, Johann Philipp; Kuhn, Gerhard; Esper, Oliver; Lembke-Jene, Lester; Winckler, Gisela (In: Struve, T et al. (2025): Sediment composition and particle flux reconstructions for the Southeast Pacific Antarctic Zone [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982690, 2025)
This dataset contains summer sea surface temperatures (SSST) and winter sea ice cover (WSI) reconstructions for core PS58/270-5 collected during R/V Polarstern expedition ANT-XVIII/5a in 2001 (Miller, 2001). The SSST and WSI were calculated using transfer functions for diatom assemblages based on the Imbrie and Kipp method (IKM) (Esper and Gersonde, 2014a) and the modern analogue technique (MAT) (Esper and Gersonde, 2014b), respectively. The reported age model is derived from diatom-based stratigraphy and correlation of the SSST and Fe content with EDC ice core data (doi:10.1594/PANGAEA.983158). This dataset uses a revised stratigraphy as section 1995-2095 cm was curated in reverse order.
Keywords: glacial-interglacial changes; iron fertilization; particle fluxes; Pleistocene; Southern Ocean; WAIS